Evaluation of the scholarship program by the education fund management institute in Indonesia - Putra, Fahdiansyah; Rahman, Abdul; Kasim, Azhar (International Journal of Evaluation and Research in Education (IJERE), 2024)
The primary objective of this investigation is to conduct a comparative analysis between the target formulation and outcomes of the Education Fund Management Institute (LPDP) scholarship program and the targeting outcomes of program model. The research paradigm employed is post-positivism, utilizing qualitative methods to explore program development and assess its effectiveness. Two key conclusions emerge from this study: i) the prescribed structure of the LPDP scholarship program is considered insufficient, marked by a focus on outcomes and activities and ii) the LPDP scholarship program's performance has fallen short of anticipated standards, primarily attributable to a significant disparity between scholarship recipients and program graduates. In light of these findings, five recommendations are proposed for future enhancements to the LPDP scholarship program: i) undertake a comprehensive study to develop a vision for addressing the human resource needs in Indonesia, taking into account regional variations, industries, professions, and scientific disciplines; ii) incorporate scholarship initiatives targeting the foundational stratum; iii) foster collaboration with ministries and institutions engaged in comparable program management and industry sectors; iv) adjust the standard of living and payment mechanisms accordingly; and v) implement stringent consequences within the LPDP framework for scholarship recipients who fail to graduate within the stipulated timeframe.